The potential role of antioxidants in mitigating skin hyperpigmentation resulting from ultraviolet and visible light‐induced oxidative stress. Issue 6 (15th October 2018) - Nahhas, Amanda F.; Abdel‐Malek, Zalfa A.; Kohli, Indermeet; Braunberger, Taylor L.; Lim, Henry W.; Hamzavi, Iltefat H.
Summary: Oxidative stress is an integral element that influences a variety of biochemical reactions throughout the body and is known to play a notable role in melanogenesis. Exogenous triggers of oxidative stress, such as ultraviolet radiation (UVR) and visible light (VL), lead to pigment formation through somewhat different pathways, but both share a common endpoint—the potential to generate cosmetically undesirable hyperpigmentation. Though organic and inorganic sunscreens are available to protect against the UVR portion of the electromagnetic spectrum, coverage is lacking to protect against the VL spectrum. In this manuscript, we review the phases of tanning, pathways of melanogenesis triggered by UVR and VL, and the associated impact of oxidative stress. We also discuss the known intrinsic mechanisms and paracrine regulation of melanocytes that influence their response to UVR. Understanding these mechanisms and their role in UVR‐induced hyperpigmentation should potentially lead to identification of useful targets that can be coupled with antioxidant therapy to alleviate this effect.